Enlightening the World : The Creation of the Statue of Liberty - Khan, Yasmin Sabina (Book collections on Project MUSE., 2010)
Conceived in the aftermath of the American Civil War and the grief that swept France over the assassination of Abraham Lincoln, the Statue of Liberty has been a potent symbol of the nation's highest ideals since it was unveiled in 1886. Dramatically situated on Bedloe's Island (now Liberty Island) in the harbor of New York City, the statue has served as a reminder for generations of immigrants of America's long tradition as an asylum for the poor and the persecuted. Although it is among the most famous sculptures in the world, the story of its creation is little known. In Enlightening the World, Yasmin Sabina Khan provides a fascinating new account of the design of the statue and the lives of the people who created it, along with the tumultuous events in France and the United States that influenced them. Khan's narrative begins on the battlefields of Gettysburg, where Lincoln framed the Civil War as a conflict testing whether a nation "conceived in liberty, and dedicated to the proposition that all men are created equal ... can long endure." People around the world agreed with Lincoln that this question-and the fate of the Union itself-affected the "whole family of man."Inspired by the Union's victory and stunned by Lincoln's death, Édouard-Rene Lefebvre de Laboulaye, a legal scholar and noted proponent of friendship between his native France and the United States, conceived of a monument to liberty and the exemplary form of government established by the young nation. For Laboulaye and all of France, the statue would be called La Liberte Éclairant le Monde-Liberty Enlightening the World. Following the statue's twenty-year journey from concept to construction, Khan reveals in brilliant detail the intersecting lives that led to the realization of Laboulaye's dream: the Marquis de Lafayette; Alexis de Tocqueville; the sculptor Auguste Bartholdi, whose commitment to liberty and self-government was heightened by his experience of the Franco-Prussian War; the architect Richard Morris Hunt, the first American to study architecture at the prestigious École des Beaux-Arts in Paris; and the engineer Gustave Eiffel, who pushed the limits for large-scale metal construction. Also here are the contributions of such figures as Senators Charles Sumner and Carl Schurz, the artist John La Farge, the poet Emma Lazarus, and the publisher Joseph Pulitzer. While exploring the creation of the statue, Khan points to possible sources-several previously unexamined-for the design. She links the statue's crown of rays with Benjamin Franklin's image of the rising sun and makes a clear connection between the broken chain under Lady Liberty's foot and the abolition of slavery. Through the rich story of this remarkable national monument, Enlightening the World celebrates both a work of human accomplishment and the vitality of liberty.